IMPACT OF FINANCIAL CRISIS 2008 ON CAPITAL STRUCTURE DECISIONS AND CORPORATE PERFORMANCE OF FIRMS LISTED ON FTSE-100 - GHAZALI, MUHAMMAD YAHYA (2012)
Financial crisis 2008 provides a unique platform to investigate the impact on the capital structure decision and corporate performance of firms listed on FTSE 100. Using the Panel data set from 2000 to 2011, this study finds significant differences in the results between pre and post-crisis period. The results suggests owing to the financial crisis 2008, firms capital structure decisions were greatly affected, altering the relationship between leverage and explanatory variables along changing the significance level. Moreover, significant differences were found when the results of Pooled OLS and fixed effect estimation were compared showing the need to control for fixed effect (Bevan and Danbolt, 2004). Analysis of financing pattern of firms listed on FTSE 100 reveals firms have adopted risk averse strategy after the financial crisis 2008 as they are more concerned about future outlook. Trend analysis using various performance measuring ratios facilitated in gaining insights of the company’s performance in pre and post-crisis periods.